Reductive Electrosynthesis of Crystalline Metal–Organic Frameworks - Li, Minyuan; Dincă, Mircea (Journal of the American Chemical Society, 2011)
Electroreduction of oxoanions affords hydroxide equivalents that induce selective deposition of crystalline metal–organic frameworks (MOFs) on conductive surfaces. The method is illustrated by cathodic electrodeposition of Zn4O(BDC)3 (MOF-5; BDC = 1,4-benzenedicarboxylate), which is deposited at room temperature in only 15 min under cathodic potential. Although many crystalline phases are known in the Zn2+/BDC2– system, MOF-5 is the only observed crystalline MOF phase under these conditions. This fast and mild method of synthesizing MOFs is amenable to direct surface functionalization and could impact applications requiring conformal coatings of microporous MOFs, such as gas separation membranes and electrochemical sensors.